Liquid Metal Yagi-Like Antenna Printed on Shape Memory Polymer Substrate for Pattern Reconfiguration - Qianyu Wang; Sicong Liu; Chunwei Li; Zhongshan Deng (IEEE Access)
In this study, a pattern reconfiguration liquid metal printed antenna is proposed. The antenna, based on the well-known Yagi-Uda antenna, is obtained by directly printing gallium-based liquid metal on a perfluorosulfonic acid ionomer (PFSA) substrate. Since PFSA undergoes two thermally reversible transitions above room temperature, thus exhibiting a triple shape memory effect, the bending state of the antenna substrate can be changed by adjusting the temperature. By changing the operating state of the antenna, the main beam of the antenna can be reconfigured in the E-plane. The proposed E-plane pattern reconfigurable antenna is simple in structure and easy to realize, and its measured results are in good agreement with the simulation results, with the gain and radiation efficiency of 4.4 dBi and 81.2%, respectively. The antenna has the advantages of simple fabrication, light weight, strong E-plane beam switching capability and high gain. These advantages make it possible to be applied in the field of pattern reconfiguration antennas.